A Study of Biomass Concrete Reinforced with Fiber Composites to Enhance Impact Load Capacity - Sakkampang, Kunanon; Tasenhog, Piyorus; Onsalung, Nirut; Huchaiyaphum, Narong (Civil Engineering Journal, 2025)
This research investigates the energy absorption from impact forces of steel reinforced concrete using fly ash obtained from agricultural processes, reinforced with glass fiber-reinforced polymer (GFRP) bars, compared to steel reinforcement. The reinforcement pattern involves incorporating GFRP bars into a square grid pattern of 4, 9, and 12 openings within bio-steel concrete with dimensions (W × L × H) of 40 × 40 × 10 cm. The testing is conducted using a Drop Test impact testing machine with a 30 kg hammer head at a velocity of 7 m/s, employing two different hammer head configurations: flat and 45-degree angled, to study energy absorption (Ea), specific energy absorption (Es), and the pattern of deformation resulting from impacts. The study finds that CBRHA-10-fiber A concrete exhibits higher energy absorption and specific energy absorption compared to steel-reinforced (CBRHA-10-steel A) concrete in the same configuration by 18.82% and 26.83%, respectively, in the flat-headed hammer impact configuration. Similarly, in the 45-degree angled hammer head configuration, CBRHA-10-fiber A concrete demonstrates superior energy absorption and specific energy absorption compared to steel reinforcement in the same configuration by 6.10% and 14.92%, respectively. In conclusion, bio-steel reinforced concrete with glass fiber-reinforced polymer (GRFP) reinforcement exhibits good load-bearing capacity and suitability as an alternative to steel reinforcement in future applications. Doi: 10.28991/CEJ-2025-011-02-020 Full Text: PDF